Aksi Terobosan Merdeka Belajar Melalui Assesmen Kompetensi Minimum dan Survey Karakter Siswa di Era Revolusi Industri 4.0 - ' Depi Elpina, Ambiyar, Ishak Aziz (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2021)
Governments realize the goals of the Education Law to improve the quality of education through curriculum of 2013. In fact, the industrial revolution 4.0, the level of education is low by world from the results of PISA test students' academic performance by the OECD was 15 years old. The government also implemented a character-based curriculum in 2013. This curriculum is targeting the development of students not only on academic intelligence, but also moral, spiritual, personality and skills. However, the implementation of this curriculum is still hobbled. Action through mapping program quality achievement of national and regional education offers an alternative democratic process in education "Independent Study", to be implemented by the government. The formulation of the problem is how the action program in the Independent Learning through minimal competency assessment and surveying character? The type of research is descriptive, the study of literature. Based on a review of relevant literature and research results obtained minimum competency assessment material analytical skills of students in literacy and numeracy and is supported by a survey study of more noble character education. It is important to do the challenges facing the globalization.Keywords: Minimum Competency Assessment, Independent Learning, Survey Characters